Velhos e novos ingredientes da questão alimentar no Brasil - Baccarin, José Giacomo [UNESP] (My University, 2008)
Conditional elements of the improvement of the income's distribution and nutritional indices in Brazil are analyzed. At the same time, it indicates there still are problems in the production and consumption of agricultural products and foods. With participation of credit, minimum price and research, the productivity and the agricultural production have grown increasing its availability per capita. Agricultural prices reduced, helping with events in the food industry and in retail so that the foods were 34% cheaper between 1994 and 2006. The competitiveness of Brazilian agriculture system is evident in the increase of its participation in the worldwide exportation. However, at the same time, the indebtedness of farmers increased. The productive success was not repeated in social terms, with a decrease in the agricultural occupation and maintenance of high concentration of the ownership of the land, in detriment of familiar agriculture. The indicators of distribution of income of the Brazilian population have been improving since 1990, based on the control of inflation, the expansion of programs of income's transference and the increase, from 2003 in front, of formal employment and minimum wage. The number of families in extreme poverty and the indices of malnutrition of children and adults have fallen. Meanwhile, the concentration of income in Brazil continues very high and important differences remain, with indicators of poverty and malnutrition being higher in rural areas, in North and Northeast and between black and brown. On the other hand, the indices of on weight and obesity being grow, even among the poorest.
Old and new ingredients of the food issue in Brazil
Keywords: Distribution of income; Food consumption; Food issue; Food production; Malnutrition.